Anxiety and depression in pediatric patients with disorder of brain-gut interaction: the role of diarrhea and abdominal pain as key determinants - Chen, Zhaodi; Chen, Qiqi; Zhou, Li (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to evaluate the prevalence of anxiety and depression in children diagnosed with disorder of brain-gut interaction (DGBI) and to examine their association with abdominal pain and diarrhea.MethodsThis study employed a mixed-methods design, combining cross-sectional surveys with longitudinal follow-up, enrolling 311 children aged 6–18 years, including 119 in the DGBI group and 192 in the non-DGBI group. Psychological status was assessed using the Screen for Child Anxiety-Related Emotional Disorders (SCARED) and the Children's Depression Inventory-Second Edition (CDI-2). Symptom diaries were utilized to document abdominal pain intensity (measured via Visual Analog Scale, VAS) and diarrhea frequency. Multivariate logistic regression analysis was performed to identify significant risk factors.ResultsThe DGBI group exhibited significantly higher prevalence rates of anxiety (40.3% vs. 16.7%, p < 0.001) and depression (33.6% vs. 12.0%, p < 0.001) compared to the non-DGBI group. DGBI were associated with a 2.09-fold increased risk of anxiety (95% CI: 1.26–3.47) and a 3.09-fold increased risk of depression (95% CI: 1.76–5.45). The intensity and frequency of abdominal pain, as well as the frequency of diarrhea, were identified as independent predictors of both depression and anxiety. Notably, harmonious family relationships were found to significantly mitigate the risk of depression in children with DGBI.ConclusionDGBI are strongly associated with elevated rates of anxiety and depression in pediatric populations, with abdominal pain and diarrhea serving as critical symptomatic drivers. Family support emerged as a protective factor against depression. These findings underscore the importance of routine psychological screening and the implementation of integrated, multidisciplinary interventions in the clinical management of DGBI.